CAFFEINE CONSUMPTION AMONG WORKERS WITH PSYCHO-EMOTIONAL RISK FACTORS - Teodorа T. Dimitrova; Darina N. Hristova; Panayot N. Nikolov (Peytchinski Publishing, 2018)
Consumption of energy drinks grows worldwide which increases the need for research and scientific prove for their safe use concerning health effects they might cause among the population. Not properly discussed remains the issue about employers who offer their employees energy drinks in the workplace without any limits. Not fully clarified are the safe levels of consumption of caffeine by workers with a high level of mental tension. The purpose is to explore coffee consumption among people working at different levels of stress in the workplace. Material and methods: A cross-sectional study of coffee consumption and working conditions was conducted with an emphasis on psycho-emotional tension among working-age people from north-eastern Bulgaria. A structured proprietary questionnaire including questions about: coffee intake and working conditions has been developed. Results: Daily consumption of coffee correlates with the following characteristics of the labour task: - Level of stress according to self-assessment 0,086 - Deficiency of time by performing daily obligations 0,121 - Risk of failure by daily tasks 0,208 - Presence of high work responsibility 0,143 Consumption of coffee among workers with high work responsibility is proven to lead to increased subjective feeling and fear of failures with serious consequences (р<0.05). Conclusions: The complex approach for the evaluation of health effects caused by the consumption of coffee includes the assessment of the risk factors due to working conditions and lifestyle.